BUGIS CULTURE-BASED LEADERSHIP IN ISLAMIC BOARDING SCHOOLS IN TRANSFORMING STUDENTS’ RELIGIOUS CHARACTER DEVELOPMENT: A STUDY AT DDI UJUNG LARE ISLAMIC BOARDING SCHOOL, PAREPARE - Abdul Malik; Nurhayati; Wirani Aisiyah Anwar; A. Rio Makkulau Wahyu; Mujahidin Usman; Aisyah Yaekaji (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyze pesantren leadership based on Bugis cultural values in transforming the religious character of students at DDI Ujung Lare Islamic Boarding School, Parepare. The primary focus of this research lies in how Bugis cultural values such as siri’, lempu’, sipakatau, and pacce are integrated into leadership practices and their impact on shaping students’ religious character. This study employs a qualitative approach with a descriptive research design. Data were collected through interviews, participatory observation, and documentation. The informants consisted of the pesantren leader, teachers, dormitory supervisors, and students. Data analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the school leadership functions not only as a policymaker but also as a primary role model in the internalization of religious values. This exemplary leadership is reflected in active involvement in religious activities, consistency between words and actions, and a humanistic and participatory communication style. The integration of Bugis cultural values in leadership is evident in the application of lempu’ (honesty and integrity), sipakatau (mutual respect), pacce (social empathy), and siri’ (discipline and self-respect). These values are not merely taught theoretically but are also implemented in the daily practices of the pesantren. Bugis culture-based leadership has proven effective in fostering a strong and sustainable religious culture. This is reflected in the habituation of worship practices, ethical social interactions, and increased student participation in religious and social activities. The process of value internalization occurs through habituation, observation, and imitation of the behaviors demonstrated by leaders and the pesantren environment. Furthermore, adaptive and persuasive leadership contributes to social stability, minimizes conflict, and fosters harmonious relationships among leaders, teachers, and students. In conclusion, this study affirms that pesantren leadership grounded in Bugis cultural values plays a strategic role in transforming students’ religious character. The integration of local cultural values into leadership practices serves as an effective model for contextual character education, rooted in local wisdom and relevant in addressing the challenges of modernization. Theoretically, this study enriches the discourse on culturally grounded educational leadership by integrating Bugis local wisdom into character education, while practically it provides a contextual leadership model that can be adopted by Islamic boarding schools and other educational institutions to strengthen students’ religious character through local cultural values